Managing Functional Basic Education for Sustainable Leadership in Nigeria - Nimota Jibola Kadir Abdullahi (Jurnal Pendidikan Humaniora, 2019)
Abstract: Purpose of the study is to identify the correlation between vocational education, basic science and technology, cultural and creative arts education and sustainable leadership in public junior secondary schools. Three hypotheses were formulated and tested. Quantitative research design was used for the study. A self-constructed questionnaire was used for data collection. The population of this study consists of 6,472 teachers in public junior secondary schools. Sample of 364 teachers were carefully chosen with the use of Research advisor table of determining the sample size of known population. Stratified random sampling technique was used to select teachers from sampled schools. The data collected were analyzed using Pearson product moment correlation coefficient statistic. The findings revealed that there was a positive and significant relationship between vocational education, basic science and technology, cultural and creative arts education and sustainable leadership. Key Words: managing, functional education, sustainable leadershipAbstrak: Tujuan dari penelitian ini adalah untuk mengidentifikasi korelasi antara pendidikan kejuruan, ilmu pengetahuan dan teknologi dasar, pendidikan seni budaya dan kreatif dan kepemimpinan berkelanjutan di sekolah menengah pertama negeri. Tiga hipotesis dirumuskan dan diuji. Desain penelitian kuantitatif digunakan untuk penelitian ini. Kuesioner digunakan untuk pengumpulan data. Populasi penelitian terdiri dari 6.472 guru di sekolah menengah pertama negeri. Sampel dari 364 guru dipilih menggunakan tabel Research advisor untuk menentukan ukuran sampel populasi yang diketahui. Teknik stratified random sampling digunakan untuk memilih guru dari sekolah sampel. Data dikumpulkan kemudian dianalisis dengan statistik koefisien korelasi product moment Pearson. Temuan penelitian adalah ada hubungan positif dan signifikan antara pendidikan kejuruan, ilmu pengetahuan dan teknologi dasar, pendidikan seni budaya dan kreatif dan kepemimpinan berkelanjutan. Kata kunci: mengelola, pendidikan fungsional, kepemimpinan berkelanjutan